Multinationals without Advantages - Massimo Motta (The Research Institute of Industrial Economics (IUI), 1996)
We propose a simple model to analyze the widespread idea that a necessary condition for firms to make foreign direct investments is that they have firm-specific advantages with respect to host country firms. We show that no such advantages are necessary to become multinationals. Further, firms might be induced to invest abroad to acquire new advantages, rather than exploiting existing ones. For this reason, foreign direct investment might occur even in the absence of exporting costs and lower production costs in the host country. Firms endowed with lower quality might make direct investments to benefit from technological spillovers which arise when manufacturing subsidiaries are close, whereas high quality firms might prefer not to invest abroad to avoid dissipation of their advantages.
Keywords: F21; F23; 330; TRANSNATIONAL CORPORATIONS; INVESTMENTS; Auslandsinvestition; Spillover-Effekt; Multinationales Unternehmen; Theorie